Detención temprana de ambliopía y consecuencias en el aprendizaje en niños de 5 a 6 años de edad en 2 escuelas fiscales de la ciudad de Machala en el año 2012 - 2013. - Jarro Sánchez, Cristhian M. (2013)
The aim of this study was to detect in children at an early age vision problems that can be reflected in their academic performance and where many times we permit this kind of discomfort in our school. This is a descriptive, observational and cross-sectional study conducted in two stages schools: Bolivia Benitez and National Union of teachers in the city of Machala during the 2012-2013 year for which students examined between 5-6 years old, of the respective site.